Primary umbilical endometriosis: To scope or not to scope - A Chrysostomou; S Branch (South African Medical Association, 2017)
Background. Primary umbilical endometriosis (PUE) is a rare condition affecting 0.5 - 1% of all cases of extragenital endometriosis. The method of using routine laparoscopic inspection of the pelvis to exclude pelvic endometriosis has been applied extensively over the years. It has been demonstrated that even patients who have had no previous pelvic surgery or caesarean section, and have no symptoms of pelvic endometriosis or history of infertility, have presented with this condition. Objective. To investigate whether patients with PUE should always undergo a laparoscopy to exclude pelvic endometriosis. Methods. The study included women presenting with a history of painful umbilical nodules or bleeding from the umbilical nodule during or after menstruation in the absence of previous surgery either for gynecological disorders or caesarean section. The study began in January 2010 and ended in December 2016. All patients underwent umbilical biopsy confirming the presence of umbilical endometriosis before the diagnostic laparoscopy took place. Results. Fourteen patients with cutaneous (scar) and umbilical endometriosis attended the clinic during the study period. Of these, only six cases (42.8%) met the inclusion criteria of PUE clinically, and underwent diagnostic laparoscopy. Their mean age was 31.1 years (range 23 - 48), and the mean parity was 1.1 (range 0 - 3), with no history of previous pelvic surgery or caesarean section. Biopsies of the lesions confirmed the presence of endometrial tissue (gland and stroma) and haemorrhage. Diagnostic laparoscopy that took place immediately after the excision of umbilical endometriosis revealed no pelvic endometriosis. Conclusion. A laparoscopy to exclude pelvic endometriosis should not be undertaken in patients who present with PUE, as there is a potential risk of introducing endometriosis into the pelvic cavity. Additionally, there is a risk of exposing the patient to unnecessary intervention and possible complications associated with the procedure.